Two lncRNAs of Chinese cabbage confer Arabidopsis with heat and drought tolerance - Yujie Wang; Shuqi Sun; Xuehuan Feng; Nan Li; Xiaoming Song (Vegetable Research)
Currently, frequent occurrences of abnormal weather events, including drought and extreme temperatures, are impacting plant growth and crop yields globally. Numerous lncRNAs in plants are known to be associated with stress responses, yet only a select few have been validated experimentally. Our prior research identified a set of lncRNAs in Chinese cabbage that were closely related to heat stress response through RNA-seq and bioinformatics analysis. In this study, two lncRNAs (lnc000283 and lnc012465) were selected for genetic transformation in Arabidopsis to elucidate their functions. Arabidopsis plants over-expressing (OE) lnc000283 and lnc012465 accumulated higher levels of anthocyanins in the later growth stage when cultivated in a culture dish. When subjected to heat stress, both OE lnc000283 and OE lnc012465 plants exhibited enhanced thermotolerance, with lnc012465 showing particularly pronounced effects. Moreover, the transgenic Arabidopsis plants demonstrated greater resistance to drought stress compared to the wild type. Under heat or drought treatments, the transgenic plants exhibited significantly higher fresh-to-dry weight ratios, POD activities, green leaf percentages, and survival rates compared to the wild type. Additionally, the transcript levels of Hsp18.1-CI were substantially elevated in the transgenic plants, both before and after heat treatment, and the expression levels of several drought-responsive genes were significantly higher than those in the wild type following drought stress. Altogether, the present results provide new ideas for the breeding of new multi-stress-tolerant varieties.